The Understanding of Large-Scale Social Restriction Policy towards Forms of Social Citizenship within the Jagakarsa Village Community - Ipani Wahdaniatun; Erna Ermawati Chotim (Publikasi Indonesia, 2022)
Jakarta is the area with the highest number of health protocol violators on the island of Java. Social citizenship emphasizes rights and obligations and requires awareness tools, social responsibilities to be articulated and represented among them through participation. The problem in this study is formulated with these questions: 1) Is there any influence of the understanding of the Large-Scale Social Restriction Policy (PSBB) on the forms of social citizenship within the Jagakarsa Village community? 2) What is the form of social citizenship of the Jagakarsa Village community during the implementation of the Large-Scale Social Restriction Policy (PSBB)? Here is the hypothesis, H0: There is no effect of understanding the policy of Large-Scale Social Restrictions on social citizenship. H1: There is an effect of understanding the policy of Large-Scale Social Restrictions on social citizenship. This research uses a mixed-method that combines quantitative and qualitative methods with an explanatory sequential strategy. Respondents and resource persons in this study are the people of Jagakarsa village. This study concludes that understanding the policy of Large-Scale Social Restrictions has an effect or gives positive results on the social citizenship variables. The Jagakarsa village community is categorized into the passive citizenship type.